Behavior of Reinforced Concrete Beams with Vertically Penetrated Holes across the Cross ‐ Sectional Depth - Khadhair, ‪Aws Yaseen‬‏; Izzet, Amer F. (Engineering, Technology & Applied Science Research, 2024)
In Iraq and other countries, RC beams are frequently used as alternative small slab penetrations in low-rise constructions. The structure is capable of transferring stresses effectively and the existence of minor gaps normally has little impact on the structural performance. However, special consideration must be given to the analysis and design of such beams depending on the effect of the openings. Hence, the objective of this paper is to address this research gap by evaluating and enhancing the behavior of RC beams with a vertical opening that penetrates the entire depth of the beams and obstructs the reinforcement bars since all the building design codes and guidelines introduce very limited recommendations for beams with vertical openings. To achieve that, five specimens were fabricated as RC beams with vertical openings and one specimen as a reference beam. The six specimens were tested under two-point loads over a clear span length of 180 cm and a total length of 200 cm. It was found that by adopting a vertical opening into the RC beam without any strengthening methods, the ultimate carrying load capacity decreased and the mid-span deflection increased compared with the reference solid beam.